ADVOCATE IMMUNITY RIGHTS IN INDONESIAN PRINCIPLES, CONCEPTS, LEGISLATION - Selamat Tambunan; Bambang Heri Supriyanto (International Journal of Social Science, 2023)
Advocate Immunity Rights In Indonesian Principles, Concepts, Legislation, the author chose this title because until now the protection of advocate immunity rights as a part of law enforcement in Indonesia, especially with regard to the protection of advocate immunity rights, still feels lacking due to several factors. The main problem in the article is to discuss how the rights of advocate immunity in principles and concepts, the rights of advocate immunity according to Indonesian law, the protection of advocate immunity rights in the Indonesian criminal law system and internal factors, namely advocate organizations including: not only one advocate organization (multy bar), different human resources, competition in providing legal services to clients, various angles of legal interests, all of which are due (motivation of Semusin) the needs, interests of each advocate organization, external factors including not yet there is an understanding regarding the right of immunity attached to advocates with other law enforcers, statutory products that do not yet provide limitations on the right of immunity possessed by advocates with good ethics who carry out their roles and functions as law enforcers, the stereotyped way of thinking of justice seeker who is still me people understand about the immunity right of a person who works as a lawyer. The methodology used in this research is literature review research, which will use a descriptive research type with a literature approach, based on the existing reality.